Religious Ripples on the Bosporus: Mediterranean History used as an Analogy for the Nineteenth-Century Kulturkampf in Ida Hahn-Hahn’s Eudoxia - Csillag, Paul (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2023)
In 1866, the German Countess Ida von Hahn-Hahn published a historical novel titled Eudoxia, die Kaiserin. Its protagonists are the fifth-century Byzantine Empress Eudoxia and a Gothic Arian princess named Gunild. Gunild was Hahn’s literary alter ego, representing the connection between Gothic and German ethnicities. In the story, the Gothic princess converts from Arianism to Catholicism, symbolizing Hahn’s own conversion from Protestantism to Catholicism. Hahn wrote a story based on historical figures of the early Mediterranean Middle Ages to express her nineteenth-century religious ideas. As a Catholic convert and writer, one of her major incentives was to convince her readers of the superiority of the Roman Church. At the time she wrote Eudoxia, conflict between Protestants and Catholics was dividing German society, leading to the so-called Kulturkampf which would fully escalate later in the 1870s. With her novel, Hahn advocated for the Catholic Church, and argued in favor of the territorial independence of the Papal States. By doing so, she was implicitly criticizing liberal, secular, and Protestant authors who favored an expropriation of the church’s earthly possessions. For the author, the Kulturkampf represented a confrontation between a controlling, conquering state and the rightful church. To explain her interpretation of current political events, Hahn used semifictional characters like Eudoxia and John Chrysostom to symbolize secular power and Catholicism respectively against a backdrop of Mediterranean history. Her historical novel is, moreover, an example of how female Mediterranean history could be used to create political narratives and how female writers of nineteenth-century Europe interacted with the southern sea’s past.